ASUHAN KEBIDANAN BAYI BARU LAHIR PADA BAYI NY. S USIA 1 HARI DENGAN CAPUT SUCCEDANEUM DI RUMAH SAKIT ELISABETH LUBUK BAJA BATAM DESEMBER TAHUN 2018 - Putri Miseri Cordias Domini Hulu; Oktafiana Manurung (STIKes Santa Elisabeth Medan, 2018)
According to Word Health Organization (WHO) data, infant mortality caused by Succedaneum Caput infection decreased by 0.05% from 4 million infants who died at 30 days (advanced neonatal). While in Indonesia the infant mortality rate due to infection of Caput succedaneum in 2013 amounted to 11% from 35 per 1000 live births. Goals: To have real experience in implementing Care of Newborn Gynecology Born on By. Mrs. S age of 1 day with Caput Succedaneum at Santa Elisabeth Lubuk Baja Batam Hospital in 2017. Method: Based on a case study on By. Mrs. S, the method uses Varney Midwifery Management approach, for data collection that is primary data consisting of physical examination include examination of caput extension, general condition, vital signs, and anthropometry. Result: Based on By case. Mrs. S with Caput Succedaneum performed handling and treatment for 4 days at Santa Elisabeth Hospital Batam. After the treatment of Caput Succedaneum and giving 20 gram Trombophop gel therapy, the baby's condition has improved and the caput problem has been resolved. Conclusion: Based on By case. Mrs. S after the management of Succedaneum Caput and minimize the removal of baby's head, the baby's condition has improved.